Electromagnetic immune phosphor-tipped fibre-optic thermometers. (1st June 2022) - Lowe, D H; Andersen, S L; Sutton, G; Camacho, J I; Copeland, M B; Kjeldsen, H; Laursen, K L
Abstract: Calibration traceability can be broken where there are significant, unquantified uncertainties. Thermometry in harsh environments using electrical sensors, such as thermocouples or resistance thermometers, can be unpredictably affected by electro-magnetic sources. For this application, phosphor based temperature sensors with fibre-optic connection have been made following two different approaches—phosphor decay time changes and phosphor emission spectral changes—and tested by bombardment with high energy electrons and by measurements in large magnetic fields. Both sets of tests showed good immunity to exposure, and with magnetic field tests significantly better than a thermocouple. Phosphor thermometry therefore has potential to retain traceability in situations where conventional sensors might fail.